DIRECT AND INDIRECT EFFECT OF GLOBALIZATION ON ECONOMIC GROWTH IN INDONESIA - İsmail KAVAZ; Araz Waleed HUSSEIN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This study aims to examine the relationship between crude oil prices, population, exports, inflation, and economic growth in Iraq based on annual time series from 1997 to 2022. As it is well known, crude oil is one of the most important resources for energy production, transportation, and various industries. Moreover, this energy source has a critical importance in terms of the international trade. Therefore, the effects of crude oil in Iraq’s economy is analyzed in this study. To achieve the degree and magnitude of the parameters used in the models, the Ordinary Least Squares method and the Johansen cointegration test are utilized. According to the empirical results of the study, while crude oil prices, population, and exports have a positive impact on economic growth, inflation has a negative impact. Additionally, a long-term relationship is found between crude oil prices, population, exports, inflation, and economic growth.as a result of cointegration test with the VAR system. Based on these results, it can be said that sustainable oil producing is very crucial in Iraq. Since the government income of Iraq relies heavily on revenue generated from oil exports, the improving and regulation activities should be considered in the oil sector. On the other hand, as the oil is finite resource, the local policymakers need to focus on researching alternative sources for exports and research the ways to boost the country’s GDP.